Intramolecular Friedel–Crafts alkylation with a silylium-ion-activated cyclopropyl group: formation of tricyclic ring systems from benzyl-substituted vinylcyclopropanes and hydrosilanes. Issue 2 (4th November 2020) - He, Tao; Wang, Guoqiang; Long, Peng-Wei; Kemper, Sebastian; Irran, Elisabeth; Klare, Hendrik F. T.; Oestreich, Martin
Abstract : Downstream to alkene hydrosilylation, the opening of the cyclopropane ring in benzyl-substituted VCPs is interlinked with an SE Ar of the aryl group. Abstract : A trityl-cation-initiated annulation of benzyl-substituted vinylcyclopropanes (VCPs) with hydrosilanes is reported. Two Si–C(sp 3 ) bonds and one C(sp 2 )–C(sp 3 ) bond are formed in this process where an intramolecular 6- endo-tet Friedel–Crafts alkylation of a silylium-ion-activated cyclopropane ring is the rate-determining key step. The reaction mechanism is proposed based on computations and is in agreement with experimental observations. The new reaction leads to an unprecedented silicon-containing 6/6/5-fused ring system. A phenethyl-substituted VCP derivative yields another unknown tricycle having 6/6/6 ring fusion by reacting in a related but different way involving a 6- exo-tet ring closure.